Uptake and leaching of sorbed ammonium during early growth of wheat - Bente Foereid; Emilio Alvarenga; Julia Szocs; Marianna Makadi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Sorption could be a way to concentrate nutrients in diluted waste streams to bring more nutrients back to agriculture. The aim of this work was to model the fate of sorbed NH4+ content in liquid waste streams by adding nitrogen (N) sorbed to a sorbent, zeolite, and study its effect on early growth and potential leaching losses. Methods A pot experiment with two soil types and wheat as test crop was conducted. Mineral N in soil was measured, and a leaching experiment performed. 15N labelled ammonium was sorbed to zeolite. The fertilizer effect was then compared to ammonium fertilizer applied the conventional way, with and without zeolite. Results Early uptake of sorbed ammonium was reduced by 56% compared to ammonium applied conventionally, and soil uptake compensated only very early. Nitrate concentration in leachates was reduced by 12% in sandy soil when N was applied sorbed to zeolite. However, leaching of water through the profile increased 71% when N was applied sorbed to zeolite, so that there was only a tendency to lower N losses when N was applied sorbed to zeolite. Conclusion Ammonium-N sorbed to zeolite is less plant available than conventionally applied N but may also be less prone to leaching losses.